Peer feedback decreases impulsive choice in adolescents with and without attention‐deficit/hyperactivity disorder. Issue 1 (25th February 2022) - van Hoorn, Jorien; de Water, Erik; Dekkers, Tycho J.; Pollak, Yehuda; Popma, Arne; Jansen, Brenda R. J.; Huizenga, Hilde M.; van Duijvenvoorde, Anna C. K.
Abstract: Background: Impulsivity is a core feature of attention‐deficit/hyperactivity disorder (ADHD). Previous work using the delay discounting task to assess impulsivity reveals that adolescents with ADHD tend to prefer a smaller‐immediate reward over a larger‐delayed reward, and this relates to problematic choices in daily life. To gain a better understanding of daily decision‐making in adolescence, it is important to examine the social context, as peers have a major influence on decisions. Peer influence often has a negative connotation, but also provides an opportunity to promote positive outcomes. To date, it is unclear if peers affect impulsive decision‐making in adolescents with ADHD, for better or for worse. Methods: The aim of this preregistered study was to examine the effect of peer feedback on impulsive choice in male adolescents with and without ADHD (ages 13–23; N  = 113). We utilized an adapted delay discounting task that was administered alone, in a social condition, and alone again. In the social condition, adolescents received either (between‐subjects) manipulated impulsive or non‐impulsive peer feedback. Impulsive peer feedback consisted of likes for choosing the smaller immediate reward, whereas non‐impulsive peers endorsed choosing the larger delayed reward. Results: Preregistered analyses showed that non‐impulsive peer feedback resulted in decreased impulsive choice, whereas impulsive peer feedback did not alter decision‐making in adolescents with and without ADHD. Explorative analyses of inattention and hyperactivity‐impulsivity symptoms in the total sample, irrespective of diagnosis, showed that lower hyperactivity–impulsivity and more inattention symptoms were associated with increased susceptibility to non‐impulsive peer feedback. Conclusions: Together, these findings indicate that peers may provide an opportunity to decrease impulsivity and emphasize individual differences in susceptibility to non‐impulsive peer feedback related to inattention and hyperactivity–impulsivity. Therefore, peer feedback may be a promising component in behavioral peer‐supported interventions in adolescents with ADHD.